Phytochemical and hypoglycemic screening of seeds and peel of nephelium longan fruits - Ripa, Farhana; Dash, Pritesh Ranjan; Nesa, Mst. Luthfun; Sheikh, Zara (© 2015 International Journal of Biochemistry, 2016)
This article was published in the International Journal of Biochemistry [©2015 International Journal of Biochemistry] and the definite version is available at: https://goo.gl/lRL2bC